Diabetes Upregulates Oxidative Stress and Downregulates Cardiac Protection to Exacerbate Myocardial Ischemia/Reperfusion Injury in Rats - Chen-Yen Chien; Ting-Jui Wen; Yu-Hsiuan Cheng; Yi-Ting Tsai; Chih-Yao Chiang; Chiang-Ting Chien (MDPI AG, 2020)
Diabetes exacerbates myocardial ischemia/reperfusion (IR) injury by incompletely understood mechanisms. We explored whether diabetes diminished BAG3/Bcl-2/Nrf-2/HO-1-mediated cardioprotection and overproduced oxidative stress contributing to exaggerated IR injury. Streptozotocin-induced diabetes enhanced hyperglycemia, cardiac NADPH oxidase p22/p67 expression, malondialdehyde amount and leukocyte infiltration, altered the mesenteric expression of 4-HNE, CaSR, p-eNOS and BAG3 and impaired microvascular reactivity to the vasoconstrictor/vasodilator by a wire myography. In response to myocardial IR, diabetes further depressed BAG3/Bcl-2/Nrf-2/HO-1 expression, increased cleaved-caspase 3/poly(ADP-ribose) polymerase (PARP)/TUNEL-mediated apoptosis and exacerbated IR-induced left ventricular dysfunction characterized by further depressed microcirculation, heart rate, left ventricular systolic pressure and peak rate of pressure increase/decrease (±dp/dt) and elevated left ventricular end-diastolic pressure (LVEDP) and Evans blue-2,3,5-triphenyltetrazolium chloride-stained infarct size in diabetic hearts. Our results implicated diabetes exacerbated IR-induced myocardial dysfunction through downregulated BAG3/Bcl-2/Nrf-2/HO-1 expression, increased p22/p67/caspase 3/PARP/apoptosis-mediated oxidative injury and impaired microvascular reactivity.